ELEMEN-ELEMEN YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN DI TIGA SEKTOR DALAM PERUSAHAAN MANUFAKTUR - Edbert, Edbert; Bangun, Nurainun (Jurnal Paradigma Akuntansi, 2025)
The discussion in this study was carried out to find out the factors that can affect the company's financial performance that consists of green accounting, liquidity, and capital structure in companies in the basic and chemical industry sectors, the various industries sector, and the consumer goods industry sector listed on the Indonesia Stock Exchange successively during the 2019-2021 period. This study used data from 32 company samples by applying purposive sampling and using Eviews software version 12 in the collection process using the data that has been published on IDX and on each website of the company. Data processing in this observation utilizes by using panel data regression equations. Based on the results of data processing, green accounting has a insignificant effect on the company's financial performance, liquidity has a negative insignificant effect on the company's financial performance, and capital structure has a significant effect on the company's financial performance.